DIAGNOSTIC COLPOSCOPIC ACCURACY BY THE GYNOCULAR AND A STATIONARY COLPOSCOPE. (2015) - Kallner, Helena Kopp; Persson, Maria; Thuresson, Marcus; Altman, Daniel; Shemer, Isaac; Thorsell, Malin; Shemer, Elisabeth Andrea Wikström
Abstract : Objectives: The aim of this study was to evaluate the diagnostic accuracy of sensitivity and specificity of cervical lesions by the low-cost, portable Gynocular colposcope and a stationary colposcope, in women referred for colposcopy with abnormal cervical cytology. Methods: A randomized cross-over clinical trial for evaluating the diagnostic accuracy in detecting cervical lesions by the Gynocular and a stationary colposcope. The Swede score systematic colposcopy system was used for evaluation of colposcopic abnormalities. Directed punch biopsy and excisional cone biopsy were used as the "gold-standard" by histologically confirmed high grade cervical lesions CIN2+ (CIN2, CIN3, CIN3+). In total, 123 women referred for colposcopy due to abnormal cervical cytology were recruited at the Department of Obstetrics and Gynecology, Danderyd Hospital, Stockholm, Sweden. The percentage agreement and the kappa statistic were calculated for Swede score by the Gynocular and a stationary colposcope. Swede scores were compared with the results from directed punch biopsy and excisional cone biopsy. Results: The Gynocular and the stationary colposcope had a high agreement of Swede scores with a Kappa statistic of 0.947, p < .0001. Punch biopsy diagnosed CIN2+ (CIN2, CIN3, and invasive cancer) in 44 (35.7 percent) women while cytology detected CIN2+ in 34 (27.6 percent) women. There were no significant differences of the sensitivity and specificity for different Swede scores by the Gynocular or a stationary colposcope in detecting CIN 2+. Conclusions: There were no significant differences in sensitivity or specificity in detecting cervical lesions by the Gynocular or stationary colposcope. The Gynocular is as accurate in diagnosing cervical lesions as a stationary colposcope.